Adventitious Root Cultures of Boesenbergia rotunda as a Source of Pinostrobin - Yusuf, Nor Azma; Mohd Rahim, Nur Salsabeela; Ahamad Azhar, Siti Zulaiha; Abd. Ghani, Khairunnisa; Sommano, Sarana; Khalid, Norzulaani (Insight Society, 2018)
Pinostrobin is the major bioactive compound from the roots of Boesenbergia rotunda, and it possesses activities against HIV, Helicobacter pylori, ulcer, leukemia and inflammatory. The present study aimed to optimize the conditions for the production of adventitious roots from B. rotunda on Murashige and Skoog (MS) solid medium. The effects of the MS strength and sucrose concentration on adventitious root growth were studied as well as the production of pinostrobin. Adventitious roots were initiated from bud explant of B. rotunda, on MS solid medium supplemented with 2.0 mg/L 1-Naphthaleneacetic acid (NAA) and were used to establish root suspension cultures. The optimum biomasses of 1.83 ± 0.21 g fresh weight were obtained with a 1/2 strength of MS medium. High pinostrobin production (3.54 mg/g) was obtained with 50 g/L of sucrose concentration. These results suggest that adventitious root cultures are suitable for the raw material for the large-scale production, which contain a high yield of the pinostrobin compound. The results also revealed that the culture condition is a good strategy for enhancing the pinostrobin content in the adventitious root cultures.